Communication in nursing and healthcare : a guide for compassionate practice - Gault, Iris; Shapcott, Jean; Luthi, Armin; Reid, Graeme (SAGE, 2017)
Communication is an essential skill for nurses, midwives and allied health professionals when delivering care to patients and their families. With its unique and practical approach, this new textbook will support students throughout the three years of their degree programme and on into practice, focussing on how to develop person-centredness and compassionate and collaborative care.